2004
DOI: 10.1176/appi.ajp.161.1.171
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label Trial of Riluzole in Patients With Treatment-Resistant Major Depression

Abstract: Although preliminary, these results indicate that riluzole may have antidepressant properties in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
183
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 297 publications
(194 citation statements)
references
References 13 publications
4
183
1
4
Order By: Relevance
“…14 A recent series of openlabelled studies and case reports demonstrated its efficacy. [15][16][17][18][19] Although the glutamatergic system may influence directly or indirectly the serotonergic and noradrenergic neurotransmission, there are only few data in the literature dealing with this interaction. NMDA receptor antagonists increase the serotonin levels in the brain.…”
Section: Glutamate In Depressionmentioning
confidence: 99%
“…14 A recent series of openlabelled studies and case reports demonstrated its efficacy. [15][16][17][18][19] Although the glutamatergic system may influence directly or indirectly the serotonergic and noradrenergic neurotransmission, there are only few data in the literature dealing with this interaction. NMDA receptor antagonists increase the serotonin levels in the brain.…”
Section: Glutamate In Depressionmentioning
confidence: 99%
“…[215][216][217] Supporting this idea, there is now preliminary evidence that riluzole, another drug that inhibits the release of glutamate, also has antidepressant properties both in MDD and BD. 218,219 Riluzole, approved by the FDA for the treatment of amyotrophic lateral sclerosis, exhibits neuroprotective properties in animal models of Parkinson's disease, NMDA receptor hypofunction neurotoxicity, ischemia and traumatic CNS injury. 212,213 NMDA receptor antagonism.…”
Section: Glutamatergic Strategiesmentioning
confidence: 99%
“…Charney's group 127,128 reported open-label efficacy for riluzole in patients with refractory depression and those with bipolar depression. Gorman's group 129 presented similar uncontrolled data for riluzole in patients with GAD.…”
Section: Drugs With Effects On Glutamatergic Neurotransmissionmentioning
confidence: 99%